두록 정자 운동학적 특성과 후보유전자 CD9 유전자와의 연관성 분석 - 정용대; 정진영(농촌진흥청 국립축산과학원; 김기현; 조은석; 유동조(농촌진흥청 축산기술연구소; 최정우; 장현준; 박성권; 사수진(농촌진흥청 축산기술연구소; 우제석(농촌진흥청 축산기술연구소 (Journal of animal reproduction & biotechnology (Online), 2016)
Cluster-of-differentiation antigen 9 (CD9) gene expressed in the male germ line stem cells is crucial for sperm–egg fusion, and was therefore selected as a candidate gene to investigate Duroc boar semen motility and kinematic characteristics. This study was performed to investigatetheir association with semen motility and kinematic characteristics. DNA samples from 96 Duroc pigs with records of sperm motility and kinematic characteristics [Total motile spermatozoa (MOT, 82.27±5.58), Curvilinear velocity(VCL, 68.37±14.58), Straight-line velocity(VSL, 29.06±6.58), the ratio between VSL and VCL(LIN, 47.36±8.42), Amplitude of Lateral Head displacement(ALH, 2.88±0.70)] were used in present study. A single nucleotide polymorphism (g.358A>T) in intron 6 was associated with MOT, VCL, VAP and ALH in Duroc population (p<0.05). Therefore, we suggest that the porcine CD9 may be used as a molecular marker for Duroc boar semen quality, although its functional effect was not clear yet. These results will improve the understanding of the functions of the CD9 in spermatogenesis within the reproductive tracts, and will shed light on CD9 as a candidate gene in the selection of good sperm quality boars. KCI Citation Count: 0